ANALISIS PENGARUH HUBUNGAN ANTARA KARAKTERISTIK PERUSAHAAN DENGAN PENGUNGKAPAN RESIKO (Studi Empiris Perusahaan Non Keuangan yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2017) - Frans Habrizons (JEM Jurnal Ekonomi dan Manajemen, 2021)
One of the important aspects of risk management is risk reporting (risk disclosure in the annual report). Companies are said to have disclosed risks if readers of the annual report are given information about opportunities or prospects, dangers, losses, threats, or exposures, which will have an impact on the company now and in the future. Non-financial listed on the Indonesia Stock Exchange (IDX) 2014-2017). The population in this study is in this study the population is the annual report of the sample company and the sustainability report published by the sample company from 2014 to 2017. All populations are taken as research samples. The variables used in this study are independent variables such as (type of industry, profitability, liquidity, and leverage) and the dependent variable is risk disclosure. This study uses analytical tools, namely: normality test, multicollinearity test, heteroscedasticity test, multiple linear regression with t-test, F-test, and coefficient of determination. The results of this study indicate that the variables of the industry type, profitability, liquidity, and leverage have a positive and significant effect on risk disclosure. Based on the t-test that the variables of the industry type, profitability, liquidity, and leverage are positively and significantly correlated with risk disclosure. This study can be concluded that there is a positive and significant effect of the type of industry, profitability, liquidity, and leverage simultaneously and partially on risk disclosure in non-financial companies listed on the IDX.